2014
DOI: 10.3390/v6072602
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Proposed Dichorhavirus Associated with the Citrus Leprosis Disease and Analysis of the Host Response

Abstract: The causal agents of Citrus leprosis are viruses; however, extant diagnostic methods to identify them have failed to detect known viruses in orange, mandarin, lime and bitter orange trees with severe leprosis symptoms in Mexico, an important citrus producer. Using high throughput sequencing, a virus associated with citrus leprosis was identified, belonging to the proposed Dichorhavirus genus. The virus was termed Citrus Necrotic Spot Virus (CNSV) and contains two negative-strand RNA components; virions accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…Citrus leprosis virus nuclear type (CiLV-N) and citrus necrotic spot virus appear to be strains of OFV based on 90% or higher genome sequence identity (Cruz-Jaramillo et al, 2014; Dietzgen et al, 2014; Roy et al, 2015). By degradome sequencing, a distinct CiLV-N isolate was also found in a herbarium citrus specimen from Florida in 1948 (Hartung et al, 2015).…”
Section: Bipartite Plant Rhabdoviruses: Dichorha- and Varicosavirusesmentioning
confidence: 99%
“…Citrus leprosis virus nuclear type (CiLV-N) and citrus necrotic spot virus appear to be strains of OFV based on 90% or higher genome sequence identity (Cruz-Jaramillo et al, 2014; Dietzgen et al, 2014; Roy et al, 2015). By degradome sequencing, a distinct CiLV-N isolate was also found in a herbarium citrus specimen from Florida in 1948 (Hartung et al, 2015).…”
Section: Bipartite Plant Rhabdoviruses: Dichorha- and Varicosavirusesmentioning
confidence: 99%
“…After the 1960s, the disease disappeared from Florida [ 6 ], but in the Southern region of South America it became prevalent occurring in most of the Brazilian citrus growing areas [ 7 , 8 ]. More recently, Bolivia, Colombia, Venezuela, all of the Central American countries and Mexico have been incorporated to the citrus leprosis distribution map [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Outside of mainland America, symptoms associated with citrus leprosis have been confirmed only in Hawaii, USA [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other viruses causing similar leprosis symptoms in Citrus and having the same transmission biology have been described. These include a virus related to CiLV‐C identified in Colombia and termed Citrus leprosis virus Cytoplasmic Type 2 (CiLV‐C2, genus Cilevirus ; Roy et al., ), a virus named HGSV‐2 (genus Higrevirus ) observed causing symptoms in Citrus volkameriana in Hawaii (Melzer et al., ) and a virus causing leprosis symptoms in citrus in Mexico and named CiNSV (genus Dichorhavirus , Cruz‐Jaramillo et al., ).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…While mandarins, lime and grapefruit are considered resistant to CiLV‐C, these citrus species, in addition to sweet orange, are susceptible to infection with the Citrus strain of OFV (Cruz‐Jaramillo et al., ; Roy et al., ,b). Lemon and sour orange have also been found naturally infected (Cruz‐Jaramillo et al., ; Roy et al., ,b) and Dieffenbachia and Swinglea are also alternative natural hosts. Sampling in non‐commercial C. sinensis orchards in Brazil identified that a further distinct rhabdovirus species with the proposed name CiLV‐N is causing there a nuclear‐type leprosis disease (Ramos‐Gonzalez et al., ).…”
Section: Pest Categorisationmentioning
confidence: 99%